Political reconfiguration in the social space: data analysis and future perspective - Battista, Daniele (Frontiers in Sociology, 2024)
This paper aims to explore the complex and sometimes controversial relationship between social media and politics. The correlation between these two areas of research has always been less linear than a simplistic narrative might suggest, mainly because of the involvement of different scientific disciplines, such as sociology, political science, communication, social psychology and computer science. The decision to explore this topic is motivated by the persistent relevance of social media platforms in the current era. This growing centrality is also due to the accelerated digitization process that occurred during the pandemic phase in the digital ecosystem. In particular, the pandemic has contributed to a significant evolution of the concept of social networks. The methodology used is based on secondary data, and the work seeks to highlight the expansion of digital space resulting from the shift from a simple place of interaction to a digital space that reconfigured the mobilization and political action of Campania’s governor Vincenzo De Luca. In conclusion, the study reveals important findings on the president’s use of social media. For example, active citizen engagement strategies through direct interaction, timely information sharing, and mobilization of online resources are evident. Therefore, it becomes necessary to ask and understand whether the potential of new social technologies is being used to cultivate critical and massive citizen participation in democratic processes or whether it is being distorted for the sole purpose of increasing or consolidating consent.